Enhancement of the Memory Effects for Nonvolatile Memory Devices Fabricated Utilizing ZnO Nanoparticles Embedded in a Si3N4 Layer - Oh, Do-Hyun; Cho, Woon-Jo; Son, Dong Ick; Kim, Tae Whan (AMER SCIENTIFIC PUBLISHERS, 2010)
ZnO nanoparticles embedded in a Si3N4 layer by using spin-coating and thermal treatment were fabricated to investigate the feasible applications in charge trapping regions of the metal/oxide/nitride/oxide/p-Si memory devices. The magnitude of the flatband voltage shift of the capacitance-voltage (C-V) curve for the Al/SiO2/ZnO nanoparticles embedded in Si3N4 layer/SiO2/p-Si memory device was larger than that of Al/ZnO nanoparticles embedded in SiO2 layer/p-Si and Al/SiO2/Si3N4/SiO2/P-Si devices. The increase in the flatband voltage shift of the C-V curve for the Al/SiO2/ZnO nanoparticles embedded in Si3N4 layer/SiO2/p-Si memory device in comparison with other devices was attributed to the existence of the ZnO nanoparticles or the interface trap states between the ZnO nanoparticles and the Si3N4 layer resulting from existence of ZnO nanoparticles embedded in the Si3N4 layer.
Keywords: SILICON NANOCRYSTALS; CONFINEMENT